Analisis Volatilitas Nilai Tukar Rupiah Dan Faktor-Faktor Yang Memengaruhi - Narwan Wahyudi Kurniawan; Siti Hodijah; Dwi Hastuti (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the volatility of the rupiah exchange rate against the US dollar and the influence of the trade balance, interest rates, and inflation on the rupiah exchange rate in both the short and long term. This quantitative study uses Generalized Autoregressive Conditional Heteroskedasticity (GARCH) analysis and the Error Correction Model (ECM) with time series data from January 2015 to August 2025. The results of this study explain that the volatility of the rupiah exchange rate is strongly influenced by short-term shocks and is not persistent. Partially, the trade balance variable has a positive and significant effect on the rupiah exchange rate in the long term. Conversely, in the short term, the trade balance has a negative and insignificant effect on the rupiah exchange rate. In both the long and short term, the interest rate variable has a positive but insignificant effect on the rupiah exchange rate. Inflation has a negative and insignificant effect on the rupiah exchange rate in both the long and short term. Simultaneously, in the long and short term, the trade balance, interest rates, and inflation variables have a significant effect on the rupiah exchange rate.